Service Quality and Sustainability: A Hybrid Framework for Malaysian Urban Consumers in Food and Beverage and Retail - Kumar, Thevan; Teck, Tan Seng; Geok, Lim Swee; Fernandez, Reynold Tom; Toh, Jason See; Veerunjaysingh, Subrun; Liau, Chee How (International Review of Management and Marketing, 2026)
This paper extends the SERVQUAL framework by incorporating environmental sustainability as a sixth dimension to evaluate its role in shaping consumer satisfaction and responsible consumption in Malaysia’s urban food and beverage (F&B) and retail sectors. This study adopted a quantitative approach by conducting survey on 200 Malaysian urban consumers. The data collected was analyzed using structural equation modelling (SEM). All participants gave electronic consent and joined voluntarily. According to the results obtained, sustainable behaviour such as ethical sourcing and waste reduction, have the most significant impact on customer satisfaction compared to traditional service quality variables. The findings suggest that consumer decision-making within emerging markets is strongly influenced by eco-conscious values. These findings provide strategic direction for managers and policymakers looking to integrate operational excellence with environmental responsibility, fostering competitiveness and advancing national sustainability agendas. This study provides an original theoretical extension which links the sustainable consumption with service quality by integrating sustainability into SERVQUAL framework. It complements Sustainable Development Goals 11 and 12 and offers empirical data from Malaysia, an understudied environment.